MEMAKNAI KEMBALI PENINGKATAN PROFESIONALISME TENAGA PENDIDIK PENDIDIKAN NONFORMAL - Septiarti, S. Wisni; Mulyadi, Mulyadi (JIV-Jurnal Ilmiah Visi, 2007)
Professionalism of the non-formal education personnel, which is understood as competency development, is a necessity. If we see from various points of view particularly from sociocultural aspects, the study on the dynamics of non-formal education personnel’s profession, becomes the essential part of this articel. The flexibility, which tends to be biased over time, age, materials or presentation approaches and sosiocultural aspects within the process of learning, becomes the reference for the personnel’s quality improvement efforts. Even though, in common public point of view, the existence of formal teachers is stronger than non-formal education personnel, but the NFE program development in reality is largely required. This happens because many people have not been served by the formal education system. In order to re-defined the meaning of professionalism of the NFE as an effort of the education quality improvement normatively, there is a necessity to improve the culture of operation and the dialogues among education personnel up to the education managers.